2019
DOI: 10.1038/s41467-019-13356-2
|View full text |Cite|
|
Sign up to set email alerts
|

Leishmania RNA virus exacerbates Leishmaniasis by subverting innate immunity via TLR3-mediated NLRP3 inflammasome inhibition

Abstract: Leishmania RNA virus (LRV) is an important virulence factor associated with the development of mucocutaneous Leishmaniasis, a severe form of the disease. LRV-mediated disease exacerbation relies on TLR3 activation, but downstream mechanisms remain largely unexplored. Here, we combine human and mouse data to demonstrate that LRV triggers TLR3 and TRIF to induce type I IFN production, which induces autophagy. This process results in ATG5mediated degradation of NLRP3 and ASC, thereby limiting NLRP3 inflammasome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 78 publications
3
88
0
3
Order By: Relevance
“…In leishmaniasis, a parasitic disease caused by Leishmania , an elevated burden of Leishmania RNA virus-1 (LRV1) in the parasite is associated with parasite dissemination and increased disease severity (43, 44). Toll-like receptors (TLRs) are innate immune-recognition receptors known to play a role in viral infection, and TLR3, which recognizes and responds to dsRNA (45), was found to be required for the induction of pro-inflammatory factors and disease exacerbation in leishmaniasis (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In leishmaniasis, a parasitic disease caused by Leishmania , an elevated burden of Leishmania RNA virus-1 (LRV1) in the parasite is associated with parasite dissemination and increased disease severity (43, 44). Toll-like receptors (TLRs) are innate immune-recognition receptors known to play a role in viral infection, and TLR3, which recognizes and responds to dsRNA (45), was found to be required for the induction of pro-inflammatory factors and disease exacerbation in leishmaniasis (43).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the role of IFN-β in the stimulation of antiviral and antiproliferative products (54), it is possible that the production of IFN-β may lead to enhanced clearing of virus-infected fungal cells from macrophages. TLR3 binds dsRNA in mammalian cells and was shown to play a critical role in disease exacerbation in leishmaniasis when the infecting Leishmania strain harbors a mycovirus (43, 44). In the case of M. sympodialis , we did not observe a requirement of TLR3 for IFN-β production in response to virus-infected strains (Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the clinical manifestations range from asymptomatic infection and various types of lesions to visceral disease. Previously, it was demonstrated that LRV1 boosts virulence of Leishmania guyanensis in humans [33,34,102,103]. The discovery of a virus in L. martiniquensis poses an important question on whether it also influences the pathogenicity of this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…infection. A recent study by de Carvalho et al 88 showed that LRV is present within L guyanensis and activates TLR3 to dampen caspase‐1 and IL‐1β production, that is, LRV+ve L guyanensis induces significantly lower levels of caspase‐1 activation and IL‐1β production by BMDM in vitro. In vivo ear infection of C57BL/6 mice with LRV+ L guyanensis resulted in increased swelling and parasite burden when compared to LRV‐ve L guyanensis ; however, these differences between LRV+ve and LRV‐ve L guyanensis are not observed during infection of Nlrp3 −/− mice.…”
Section: Consequences Of Nlrp3 Inflammasome Activation In Leishmaniasismentioning
confidence: 99%
“…In reviewing all known articles that show a protective role for the NLRP3 inflammasome, 56,64,76,82,88,89 we noted that these studies exclusively use C57BL/6 mice, and NLRP3 inflammasome‐deficient mice backcrossed to C57BL/6 as mammalian hosts. Regarding Leishmania spp., these studies mostly use new‐world Leishmania spp.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%